Matrix-induced autologous chondrocyte implantation versus autologous matrix-induced chondrogenesis for chondral defects of the talus: a systematic review. Issue 1 (3rd May 2021) - Migliorini, Filippo; Maffulli, Nicola; Baroncini, Alice; Knobe, Matthias; Tingart, Markus; Eschweiler, Jörg
Abstract: Introduction: Chondral defects of the talus are common and their treatment is challenging. Source of data: Recent published literatures. Areas of agreement: Membrane-induced Autologous Chondrocyte Implantation (mACI) and Autologous Matrix-Induced Chondrogenesis (AMIC) have been proposed as management for chondral defects of the talus. Areas of controversy: It is debated whether AMIC provides greater outcomes compared to mACI for chondral regeneration. Several clinical studies showed controversial results, and the best treatment has not yet been clarified. Growing points: To investigate whether AMIC provide superior outcomes than mACI at midterm follow-up. Areas timely for developing research: AMIC exhibits similar clinical results to mACI. However, AMIC involves one single surgical procedure, no articular cartilage harvest and hence no morbidity from it, no need for chondrocyte expansion in a separate laboratory setting. For these reasons, AMIC may be preferred to mACI.